Islam dan Sains Menurut Sayyed Nasr - Maulidatul Nabila; Mutia Tsamratus Sabrina; Alfina Wildatul Fitriyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
One of the greatest forms of civilization is mastering the field of science. Islam is the last religion on earth. Of course, he has teachings that his people should obey. Islam directs its people to study all kinds science for social purposes. Islam also cannot deny that its people should study science for the sake of sustainability. Islamic civilization and it was taught by the Abbasid daulah. However, there are also various sects in Islam who reject it. The existence of science within the body of Islam, especially the traditionalist group which is puritanical in nature. As time progressed the West as superpowers ruling the world, became kings in the land of Islam because of their prowess in mastering science and the Islamic ummah only saw and reflected on his backwardness from Westerners without wanting to try to rise from his downturn. Nasr emerged as a pioneer of Islamic science to restore the glory of Islam in the past, he considered Western science to be very secular arid and actually destroying the world's ecosystem. Nasr offers a combination of science and Islam so that science feels beautiful and not rigid through Islamic teachings with a Sufistic approach.